Factors lead to misbehaviour in class according to students’ perception at UiTM Seremban 3 / Mohd Dzikri Saharizan, Marsya Maizura Mohd Sam and Nur Syafiqah Md Kahar - Saharizan, Mohd Dzikri; Mohd Sam, Marsya Maizura; Md Kahar, Nur Syafiqah (2021)
This study was conducted to describe the factors that lead to misbehaviour in class according to the students’ perception in Universiti Teknologi Mara (UiTM) Seremban 3. 372 students were surveyed regarding their perception toward the factors that lead to misbehaviour in class. There are ﬁve factors that the researchers want to study which are lecturer’s personality, student’s lifestyle, inﬂuence from social media, student’s time management, and facilities. This study used several methods to analyze the research objectives. The Spearman Correlation method was used to analyze the relationship between the factors that affect the students’ perceptions on misbehaviour in class. The analysis shows that the relationship for lecturer’s personality has a moderate positive relationship, while the other four factors such as student’s lifestyle, inﬂuence from social media, student’s time management, and facilities have weak positive relationship with students’ perception of misbehaviour in class. In addition, this study also aims to identify the factors that lead to misbehaviour in class according to students’ perceptions. To achieve this objective, this study used the Multiple Linear Regression analysis and the results show that there are three factors that lead to misbehaviour in class. Those factors are lecturer’s personality, inﬂuence from social media, and student’s time management. Moreover, the Kruskal Wallis test was used to identify the ﬁnal objective which is to identify the differences in students’ perceptions between difference faculties in UiTM Seremban 3. The results show that all of the students in the three faculties have the same perceptions toward factors that lead to misbehaviour in class. For future researchers, they can use a different data collection method such as face to face interview for the same research, but perhaps for a different population.